(untitled) (International Journal of Food and Nutritional Sciences, 2022)
There is a lot of pressure on HR managers around the world to move away from traditional methods of managing human resources and integrate HR functions with business strategies through technology in order to have an impact on business performance in the current era of growing competition and constantly changing technology